LEKSIKON TANAMAN OBAT DALAM KITAB PRIMBON BETALJEMUR ADAMMAKNA (KAJIAN EKOLINGUISTIK) - Muhamad Agus Prasetyo (JP : JURNAL PENDIDIKAN, 2021)
The research purpose is to describe grammatical categories, grammatical forms, and survival of medicinal plant lexicon in the Kitab Primbon Betaljemur Adammakna (KPBA). Then explain relationship of that medicinal plants with life of Javanese people. This research use exploratory sequential mix method consists first phase, data collection using documentation techniques and analyzed by morphological theory, while the second phase is collecting data using questionnaires and analyzed by scoring techniques, then interpreted and concluded. The research data is chapter 75 of KPBA which was chosen because it contains dominant medicinal plant lexicon. The research results include (1) from 32 lexicon of medicinal plants found, all of them are categorized as grammatical nouns and grammatical forms of basic words, while their survival shows 13 safe lexicon, 7 threatened lexicon, and 12 missing lexicon; (2) relationship between that medicinal plants with life of Javanese people is culturally very close, as indicated by intense use of medicinal plant in all phases of life, as well as the abundance of Jamu lexemes and how to process medicinal plants. On the other hand, by spiritually and religiously the application of medicinal plants as Jamu always involves power of God and Javanese numerological calculations.